Motivators and inhibitors to e-Commerce adoption among women information technology IT professionals / Che Bunga Mohamed Ismail - Mohamed Ismail, Che Bunga (Fakulti of Information Technology nd Quantitative Sciences, 2007)
The growth of the World Wide Web (WWW) has paved way to the rise of Business to Commerce (B2C) electronic commerce (E-commerce). In spite of many positive predictions, B2C e-Commerce somehow does not fulfill the expectations to develop in parallel with the growth of Internet penetration. This study had identified the motivators and inhibitors of e-commerce adoption among women IT Professionals. The findings were gathered in the area that e-commerce infrastructure is reliable. The main contribution to the motivators is perceived trust. The attribute influence to this factor is respondent trust that E-Commerce financial transaction is secure and E-Commerce merchant will protect the respondent personal information from any improper data usage. In spite of many positive predictions towards this matter, there are still rejections from certain groups of user. This happen even though they are a computer literate person. There are a few factors that inhibit them from using e-commerce. In this case, the main inhibitor among women IT Professionals is lack of shopping enjoyment. This study had provided the information that will not only illustrate a new dimension to E-Commerce adoption among women IT Professionals but also widen the knowledge and understand the consumer behavior especially among women with the background of Information Communication and Technology (ICT) literate.